Culture-Dependent and Sequencing Methods Revealed the Absence of a Bacterial Community Residing in the Urine of Healthy Cats - Balboni, Andrea; Franzo, Giovanni; Bano, Luca; De Arcangeli, Stefano; Rizzardi, Alessia; Urbani, Lorenza; Segatore, Sofia; Serafini, Federica; Dondi, Francesco; Battilani, Mara (Frontiers in Veterinary Science, 2020)
A growing number of studies suggest that the lower urinary tract of humans and dogs can harbor a urinary microbiota. Nevertheless, a certain concern has developed that the microbiota reported could be due to unaccounted contamination, especially in low-biomass samples. The aim of this study was to investigate the bacterial community which populates the urine of healthy cats using two approaches: a culture-dependent approach which consisted of the expanded quantitative urine culture (EQUC) techniques capable of identifying live bacteria not growing in standard urine cultures, and a culture-independent approach which consisted of 16S ribosomal RNA next generation sequencing (16S rRNA NGS) capable of identifying bacterial DNA and exploring microbial diversity with high resolution. To avoid confounding factors of possible bacterial contamination, the urine was sampled using ultrasound-guided cystocentesis, and several sample controls and negative controls were analyzed. The urine sampled from the 10 cats included in the study showed no bacterial growth in the EQUC procedure. Although several reads were successfully originated using 16S rRNA NGS, a comparable pattern was observed between urine samples and the negative control, and no taxa were statistically accepted as non-contaminant. Taken together, the results obtained allowed stating that no viable bacteria were present in the urine of healthy cats without lower urinary tract disease and urinary tract infections, and that the bacterial DNA detected was of contaminant origin.